Thermodynamic analyses and multi-objective optimization of operation mode of advanced adiabatic compressed air energy storage system. (15th October 2018) - Han, Zhonghe; Guo, Senchuang; Wang, Shan; Li, Wei
Highlights: Mode 4 has the highest exergy efficiency. Mode 2 has the largest exergy density. Second heat exchanger has the largest exergy destruction. Abstract: Advanced adiabatic compressed air energy storage system plays an important role in smoothing out the fluctuated power from renewable energy. Under different operation modes of charge-discharge process, thermodynamic behavior of system will vary. In order to optimize system performance, four operation modes of charge-discharge process are proposed in this paper. The performance difference of four modes is compared with each other based on energy analysis and exergy analysis. The results show that exergy efficiency of mode 4 is the highest, 55.71%, and exergy density of mode 2 is the largest, 8.09 × 10 6 J m −3, when design parameters of system are identical. The second heat exchanger has the most improvement potential in elevating system performance. In addition, a parametric analysis and multi-objective optimization are also carried out to assess the effects of several key parameters on system performance.